Abernethy malformation associated with Caroli's syndrome in a patient with a PKHD1 mutation: a case report - Xiao-xiao Mi; Xiao-guang Li; Zi-rong Wang; Ling Lin; Chun-hai Xu; Jun-ping Shi (BMC, 2017)
Abstract Background Abernethy malformation is a rare congenital anomaly characterised by the partial or complete absence of the portal vein and the subsequent development of an extrahepatic portosystemic shunt. Caroli's disease is a rare congenital condition characterised by non-obstructive saccular intrahepatic bile duct dilation. Caroli's disease combined with congenital hepatic fibrosis and/or renal cystic disease is referred to - Caroli's syndrome. The combination of Abernethy malformation and Caroli's syndrome has not been reported previously. Case presentation We present the case of a 23-year-old female who was found to have both type II Abernethy malformation and Caroli's syndrome. Radiological imaging was performed, including computed tomography with three-dimensional reconstruction and magnetic resonance imaging with (magnetic resonance cholangiopancreatography (MRCP), which revealed a side-to-side portocaval shunt, intrahepatic bile duct dilation, congenital hepatic fibrosis, and renal cysts. In addition, PKHD1 (polycystic kidney and hepatic disease 1) gene mutational analysis revealed a paternally inherited heterozygous missense mutation (c.1877A > G, p.Lys626Arg). A liver biopsy confirmed the pathological features of Caroli's syndrome. Conclusions To our knowledge, this is the first reported case of a patient with both type II Abernethy malformation and Caroli's syndrome diagnosed using a comprehensive approach that included imaging, mutational analysis, and liver biopsy. Additionally, this is the second reported case to date of an Asian patient presenting with liver and renal disorders with the same paternally inherited PKHD1 missense mutation.